Economic costs of climate change and effects beyond GDP: A model-based analysis of climate change impacts in Germany - Saskia Reuschel; Britta Stöver (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2023)
Climate change impacts are already noticeable today. Their future effects and costs is of increasing intrest and a growing number of research papers hence investigate climate change impacts and climate change adaptation. However, research focused mainly on the US economy and or on the agricultural sector. Other papers concentrated on the losses in GDP. Against this background, this paper examines the macro-economic costs of climate change in Germany taking also social dimensions such as SDG indicators into account. We used a model-based scenario-analysis that allowed us to identify the costs of climate change on sectoral level and on level of different household types. The impact of three intensities of climate change (low, medium, high) was assessed on GDP, on selected indictors of the UN sustainable development goals (SDGs) as well as on inequality using household income of different household types. The findings of this study indicate that the economic costs of climate change measured by the changes in GDP have the potential to be substantially high even under conservative assumptions. Strong effects on GDP are triggered in particular by those climate effects that lead to significant price increases such as yield losses in agriculture, damages to buildings and infrastructure and impariments in international trade. The results also indicate that it is worthwhile to assess socioeconomic effects beyond GDP: climate change would increase income inequality and deteriorate in particular national SDG indicators 2 (Zero Hunger) and 10 (Reduced Inequalities). The results illustrate the high need for action in climate mitigation and adaptation and highlight the importance of taking into account not only macroeconomic effects but also social dimensions.
Keywords: 330; climate change; impact assessment; SDG; model-based scenario analysis; macro-econometric input output model